Silent myocardial infarction secondary to cardiac autonomic neuropathy in a patient with rheumatoid arthritis - Unnikrishnan, Dileep (BMJ Case Rep, 2016)
An 83-year-old female patient with rheumatoid arthritis and hypertension presented to the emergency department with fever and chills of 1 day duration. On examination, temperature was 100.9 F, heart rate 111/min and she had orthostatic hypotension. Laboratory tests showed elevated blood urea nitrogen and white cell count. The patient underwent treatment for symptomatic urinary tract infection and while her fever and leucocytosis resolved, tachycardia persisted. An EKG done showed T inversions in leads II, III, arteriovenous fistula, V2 and V3. Troponin-I was elevated. Nuclear stress test revealed apical wall motion abnormality confirming myocardial infarction. Ewing's tests were carried out at bedside and these diagnosed severe autonomic neuropathy. Rheumatoid arthritis can cause cardiac autonomic neuropathy from chronic inflammation. This case entails the importance of assessing and detecting cardiac autonomic neuropathy in chronic inflammatory conditions, and the need to be cautious of acute coronary events in these patients, even for minimal or no symptoms.